Unsur Intrinsik dan Ekstrinsik dalam Syair Lagu Tanö Niha Omasi’ö - Niar Syam Zebua; Lestari Waruwu; Noibe Halawa (STKIP PGRI Ponorogo Press, 2026)
This study aims to analyze the intrinsic and extrinsic elements contained in the lyrics of the Nias traditional song Tanö Niha Omasi’ö. Traditional songs, as a form of oral literature, play an important role in reflecting cultural identity, social values, and the worldview of the supporting community. This research employs a descriptive qualitative method with the song lyrics as the main object of study. Data were collected through reading, note-taking, and classifying lyric segments related to intrinsic and extrinsic elements. The findings reveal that the intrinsic elements include the theme of love for the homeland, messages about preserving unity and tradition, poetic diction in the Nias language, metaphorical language style, an atmosphere of pride and emotional attachment, visual imagery, the setting of Nias land, and a collective point of view representing the community. Meanwhile, the extrinsic elements encompass the cultural and social background of the Nias people, who highly value tradition, solidarity, and kinship, as well as the geographical condition of Nias as an archipelagic region influencing their perspective on land as a source of life. Therefore, the song Tanö Niha Omasi’ö serves not only as entertainment but also as a medium for cultural transmission and the reinforcement of Nias cultural identity.